The Art of Ceramic Extrusion - Händle, Frank (Springer International Publishing : Imprint: Springer, 2019)
This book is ideal for practitioners and managers with low experience in the field. It introduces the theme of extrusion in ceramics and provides checklists, questionnaires, as well as the related literature and websites covering the topic. This Brief is written in a simple language and covers topics such as honeycombs, ceramic filters, auger geometry, wear and tear.